PSI-14 The effect of creep feed and its nutrient level on growth performance in suckling and weaning pigs. (30th November 2020) - Isensee, Paige K; Albers, Sarah; Wichman, Lindsey; Thoma, Autumn; Jang, Young Dal
Abstract: Two experiments were conducted to evaluate the effect of creep feed (CF) and its nutrient level on growth performance of suckling and weaning pigs. In Exp. 1, eight litters (d 20 of age) were allotted to 2 treatments based on breed, litter size and weight as follows: no-CF (n=3) and CF (n=5; offered from 8 days before weaning). At weaning (d 28 of age), the pigs were divided into 3 treatments (6 pigs/pen, 3 replicates; initial BW: 9.66±0.34 kg) balanced with gender, weight, and breed as follows: eaters, noneaters, and no-CF. In Exp. 2, seven litters (d 12 of age) were allotted to 2 treatments as follows: HN (n=4): CF with fish meal (3%), blood meal (2.4%), and whey (15%), and LN (n=3): CF without those ingredients. At weaning (d 25 of age), eater pigs were divided into 2 treatments (6 pigs/pen, 3 replicates; initial BW: 7.53±0.97 kg) as follows: HN-eaters and LN-eaters. In both experiments, the pigs were fed a common nursery diet for 21 days. The CF was mixed with 1% Cr2 O3 to measure fecal color for eater/noneater categorization. Piglet weaning weight was not different among eaters and non-eaters in both experiments (in Exp. 1, P=0.99; 9.35, 9.33, and 9.20 kg for eaters, noneaters, and no-CF, respectively). There was no difference on overall nursery growth performance in both experiments. The HN-eaters tended to have greater ADG (P=0.08; 0.506 vs. 0.427 g/d for HN-eaters and LN-eaters, respectively) and G:F (P=0.09; 0.889 vs. 0.717, respectively) than LN-eaters in d 7-14 postweaning in Exp. 2. The CF intake and percentage of eaters/litter (P=0.60; 85.6 and 80.87% for LN and HN, respectively) in Exp. 2 were not different between treatments. In conclusion, CF did not affect overall piglet growth in suckling and nursery phases, but nutrient level might affect early nursery pig growth.